Assessment of infrastructure facilities, manpower and services at health sub-centres from a rural block of Haryana, North India - Bashar, M. D. Abu (International Journal Of Community Medicine And Public Health, 2022)
Background: A sub-centre is the most peripheral and first point of contact between the health care system and the Community. The success of any nationwide programme largely depends on well-functioning sub-centres providing services of acceptable standard to people. Indian Public Health Standards (IPHS) were programmed with an objective to standardize the health care infrastructure and services. Current study was undertaken with the aim to assess the infrastructure facilities, manpower and services of a sample of sub-centers from North India against the IPHS standards. Methods: A cross sectional study was carried out from February 2014 to October 2014 in 30 of the 32 sub-centres in a rural block of district Ambala in the state of Haryana, North India using a specially designed semi structured questionnaire to compare the existing physical infrastructure, manpower, quality control and service delivery in these sub-centres against the IPHS standards. Results: Significant gaps existed in available physical infrastructure and availability of manpower (especially male worker). The parameters designed for quality control like citizen’s charter, internal and external monitoring were also found to be deficient. Record keeping and reporting was also unsatisfactory. However, availability of the requisite services and service delivery was found to be satisfactory. Conclusions: There is urgent need to equip the sub-centres with the necessary infrastructure and logistics along with need of regular monitoring and supervision of the sub-centers by internal and external agencies so as to improve the quality of facilities and services provided by them.